Inhibition of LC3-associated phagocytosis in COPD and in response to cigarette smoke. (October 2021) - Asare, Patrick F.; Tran, Hai B.; Hurtado, Plinio R.; Perkins, Griffith B.; Nguyen, Phan; Jersmann, Hubertus; Roscioli, Eugene; Hodge, Sandra
Introduction/Rationale: In chronic obstructive pulmonary disease (COPD), defective macrophage phagocytic clearance of cells undergoing apoptosis by efferocytosis may lead to secondary necrosis of the uncleared cells and contribute to airway inflammation. The precise mechanisms for this phenomenon remain unknown. LC3-associated phagocytosis (LAP) is indispensable for effective efferocytosis. We hypothesized that cigarette smoke inhibits the regulators of LAP pathway, potentially contributing to the chronic airways inflammation associated with COPD. Methods: Bronchoalveolar (BAL)-derived alveolar macrophages, lung tissue macrophages obtained from lung resection surgery, and monocyte-derived macrophages (MDM) were prepared from COPD patients and control participants. Lung/airway samples from mice chronically exposed to cigarette smoke were also investigated. Differentiated THP-1 cells were exposed to cigarette smoke extract (CSE). The LAP pathway including Rubicon, as an essential regulator of LAP, efferocytosis and inflammation was examined using western blot, ELISA, flow cytometry, and/or immunofluorescence. Results: Rubicon was significantly depleted in COPD alveolar macrophages compared with non-COPD control macrophages. Rubicon protein in alveolar macrophages of cigarette smoke-exposed mice and cigarette smoke-exposed MDM and THP-1 was decreased with a concomitant impairment of efferocytosis. We also noted increased expression of LC3 which is critical for LAP pathway in COPD and THP-1 macrophages. Furthermore, THP-1 macrophages exposed to cigarette smoke extract exhibited higher levels of other key components of LAP pathway including Atg5 and TIM-4. There was a strong positive correlation between Rubicon protein expression and efferocytosis. Conclusion: LAP is a requisite for effective efferocytosis and an appropriate inflammatory response, which is impaired by Rubicon deficiency. Our findings suggest dysregulated LAP due to reduced Rubicon as a result of CSE exposure. This phenomenon could lead to a failure of macrophages to effectively process phagosomes containing apoptotic cells during efferocytosis. Restoring Rubicon protein expression has unrecognized therapeutic potential in the context of disease-related modifications caused by exposure to cigarette smoke.